A Development of Problem Based Learning Based Vlog to Train Critical Thinking of 10th Grades Students in Environmental Change Topic - Bunga Tiara Yulas; Fida Rachmadiarti (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2023)
Vlog (Video Blog) media is creative content presented by vloggers which are packaged in the form of videos with blog-like characteristics but the appearance and presentation are made as attractive and as good as possible for further distribution to students to facilitate the learning process. Vlog media developed using Problem Based Learning (PBL) in which at each stage there are indicators of critical thinking skills that are trained. The focus of this research is on environmental change material. This research aims to produce Vlog media based on Problem Based Learning (PBL) on environmental change material to train valid and practical students' critical thinking skills. The parameters measured in media validity are content feasibility, presentation, discussion, and suitability for the PBL stage as well as critical thinking indicators. While the parameters for practicality are the implementation of the learning stages and student responses to the characteristics of Vlogs in learning. Data analysis from validation results, implementation of learning activities, and student responses in a quantitative descriptive manner. This research is development research that refers to the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research was piloted on a limited basis with 20 10th grade students at Al-Islam Krian High School. The validation results show that the Vlog media is considered very valid with a validation score of 86%. The practicality of Vlog media is measured based on the implementation of Vlog media in learning with very practical results for use in learning with a 98% implementation and student responses with an average score of 86% in the very practical category. Thus the PBL-based Vlog media is stated to be very valid and practical to use in learning about environmental change topics. Keywords: Vlog media, problem based learning, critical thinking, environmental changes.